COULD TOURISM CARRYING CAPACITY BE A VITAL ASSET TO RESPOND TO CLIMATE CHANGE? (International Association of Biologicals and Computational Digest, 2022)
Tourism is today one of the world’s largest industry. Tourism activities can generate both positive and negative effects on the conditions of the areas where visiting and fruition activities take place. Every form of human use of natural environment causes changes to the environment conditions. There is significant change in the scale, frequency and character of the visitors over the past few decades reflect new pressure on environment and the tourist destination. Today rapid trend of tourism along with the urbanization and other factor affect climate, so sustainable tourism is necessary. Sustainability has become an important policy issue in tourism, it grows discussion and criticism and increase need to understand nature of the limit of growth. Tourism mainly causes biophysical and social impact. In many cases scientist and planners have turned to the concept of tourism capacity as the way of formulating problem and management action to identify limits of a system to absorb changes. Carrying capacity is ultimately assessment tool for the exploration of natural and artificial resource which contributes to growth of tourism. Tourism carrying capacity has shifted now from a one-dimensional approach to incorporating environmental, social and political aspect.
Keywords: Tourism, climate change, sustainable tourism, carrying capacity, tourism carrying capacity